KONSTRUKSI MAKNA SELF-CONFIDENCE DALAM FILM ANIMASI ENCANTO - Fuadiyah, Layinatul; Afyatul Masruroh, Sayidah (Spektra Komunika : Jurnal Komunikasi & Dakwah, 2024)
This research aims to uncover the meaning of the sign of self-confidence in the animated film Encanto using the semiotic approach of Roland Barthes and the theory of meaning by Wendell Johnson. The two main issues addressed are the meaning of self-confidence signs in the film and the construction of that meaning. Through a qualitative approach, an analysis is conducted on ten scenes in the film "Encanto" that contain the meaning of self-confidence. The results of the study indicate that the process of self-confidence meaning aligns with Wendell Johnson's theory, which depicts that meaning exists within oneself, changes, requires reference, is susceptible to abbreviation, is limitless, and is communicated partially. This study provides insights into how animated films can convey and build the meaning of self-confidence to their audience.